(3aJM GdQMef aj Ydei GdeYGfi hGdHjGfs - (3GdfhOgj , eMeO eYQha Hf eUWaj Hf CMeO GdTgQRhQj GdHQRfLj,J (B1254 (3g` s
(3ChdgG (B:s
(3Hbhd eYQha QHg ef Ydjg HUaGA bdHg agfGc ai GdHjGf hGdeYGfi eXekG gh GdaJM ef GdQMef s
(3BNQgG (B:s
(3HGH GdcfGjI Ydi CUhd Gdaf ai cQGSI dWjaI ai ZGjI GdfaGSI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B41s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B164s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI (B604) s
Keywords: (3GdHdGZIs